Association-Sponsored Higher Education for Business: Perceptions of First-Year Students - Wright, Phillip C.; Palmer, Robert A. (Canadian Journal of Higher Education, 1988)
Association-sponsored learning programs comprise a significant but largely unknown sector of higher education. In North America, for example, almost 500 associations are involved in the education! certification process. This paper begins the process of discovering why individuals enroll in such programmes, rejecting the many other vocationally oriented opportunities available to them. Using data from first-year students enrolled with the Canadian Institute of Management, it was found that the majority were drawn to the Institute through personal business contacts. As well, although other alternatives were investigated, the Institute's reputation, level of difficulty, the perceived "practical" nature of the courses and programme length attracted most students. As to perceptions of “utility," the Institute's learning programme was ranked just below a university degree in management and somewhat higher than a degree in a "non- management" discipline.